In vitro, in silico and network pharmacology mechanistic approach to investigate the α-glucosidase inhibitors identiﬁed by Q-ToF-LCMS from phaleria macrocarpa fruit subcritical CO2 extract - Rashid Mia, Md. Abdur; Ahmed, Qamar Uddin; Ferdosh, Sahena; Helal Uddin, A.B.M.; Awal, Md. Shihabul; Sarian, Murni Nazira; Sarker, Md. Zaidul Islam; Zakaria, Zainul Amiruddin (MDPI, 2022)
The fruit of Phaleria macrocarpa have been traditionally used as an antidiabetic remedy in Malaysia and neighbouring countries. Despite its potential for diabetes treatment, no scientiﬁc study has ever been conducted to predict the inhibitor interaction of the protein α-glucosidase identiﬁed in an extract prepared with a non-conventional extraction technique. Hence, the major aim of this research was to evaluate the in vitro antioxidant, the α-glucosidase inhibitors, and the molecular dynamic simulations of the α-glucosidase inhibitors identiﬁed by Quadrupole Time-of-Flight Liquid Chromatography Mass Spectrometry (Q-ToF-LCMS)analysis. Initially, dry fruit were processed using non-conventional and conventional extraction methods to obtain subcritical carbon dioxide extracts (SCE-1 and SCE-2) and heating under reﬂux extract (HRE), respectively. Subsequently, all extracts were evaluated for their in vitro antioxidative and α-glucosidase inhibitory potentials. Subsequently, the most bioactive extract (SCE-2) was subjected to Q-ToF-LCMS analysis to conﬁrm the presence of α-glucosidase inhibitors, which were then analysed through molecular dynamic simulations and network pharmacology approaches to conﬁrm their possible mechanism of action. The highest inhibitory effects of the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical and α-glucosidase on SCE-2 was found as 75.36 ± 0.82% and 81.79 ± 0.82%, respectively, compared to the SCE-1 and HRE samples. The Q-ToF-LCMS analysis tentatively identiﬁed 14 potent α-glucosidase inhibitors. Finally, ﬁve identiﬁed compounds, viz., lupenone, swertianolin, m-coumaric acid, pantothenic acid, and 8-C-glucopyranosyleriodictylol displayed signiﬁcant stability, compactness, stronger protein-ligand interaction up to 100 ns further conﬁrming their potential as α-glucosidase inhibitors. Consequently, itwasconcludedthattheSCE-2possessesastrong α-glucosidase inhibitory effect due to the presence of these compounds. The ﬁndings of this study might prove useful to develop these compounds as alternative safe α-glucosidase inhibitors to manage diabetes more effectively.